Nilai-Nilai Moral Dalam Novel KKN Di Desa Penari Karya Simpleman Dan Implikasinya dalam Pembelajaran Bahasa Indonesia - Ari Julian Pratama; Ermawati Arief (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
This study aims to describe the relationship of moral values with God, the relationship of human moral values with themselves, and the relationship of human moral values with other humans contained in the novel KKN in Desa Penari by Simpleman. This research is a qualitative type with descriptive method. The data in this study are data obtained from the speech of the characters, and the actions of the characters contained in the novel KKN in Desa Penari by Simpleman. The data source in this research is the novel KKN in Desa Penari by Simpleman. The instrument of this research is the researcher himself. Based on the results of the analysis, there are 23 moral values related to man's relationship with God. Moral values related to man's relationship with himself are found in 36 data. And also found moral values related to human relationships between fellow humans as much as 47 data. The implication in Indonesian language learning is that it can be implied through the Learning Implementation Plan (RPP) and Teaching Material with KD 3.9 analyzing the content and language of the novel read with the indicator that students can identify intrinsic, extrinsic and linguistic elements in a novel